Lighting Enclosed Internal Corridors By Borrowed Daylight - Abuzarifa, Narjes S M (2021)
Enclosed internal corridors are long circulation areas with no window provisions, and they require electric lighting to be switched on for 24 hours continuously to operate. Depending on the designs, some corridor designs have openings for daylight at the ends, while others supplement daylight at the middle. Most parts of these corridors, however, are usually dark and consuming a lot of non-renewable energy from artificial light. This research explores how enclosed internal corridors could get the benefits of daylight depending on the corridor wall designs. It explored how %DF (Daylight Factor) less than 1%, especially in Malaysia where the skies are bright, could still be beneficial and useful. The standard illumination required for corridors is benchmarked. Fieldwork for %DF measurements was conducted in selected points at an enclosed corridor of a hostel building on a typical overcast day. A scaled model of similar design was built and experimented with in the artificial sky to get the same set of readings; followed by simulation using Radiance. Results showed that the readings calibrate well between fieldwork compared to the scaled model and simulation, with less than 10% differences. Corridor walls are usually opaque resulting in very dark situations relying solely on artificial lighting. The study further investigated the extent of daylight that can be borrowed to illuminate the internal enclosed corridors. This was carried out by experimenting on the various types of corridor wall designs with added transparent or glazed areas to enable daylight penetration.